(untitled) (Altre Modernità, 2018)
The advent of ‘Cool Britannia’ during the height of the New Labour era in Britain transformed the image of London into that of a progressive, open and dynamic city, empowering the youth and their contribution to mainstream culture while still preserving a connection to cultural heritage. This paper analyses London as a global city and delineates it as a focal point of cultural, racial and ethnical diversity in the films Wild West (1992), Bend It Like Beckham (2002), Bride & Prejudice (2004) and Brick Lane (2007). The aim of this article is to explore cinematic representations of immigrant communities living outside the recognizable West End which anticipate or epitomize the multicultural doctrine and cultural policy of personal responsibility promoted under the Blair administration. These films oscillate between presenting a ‘cruel’ and a ‘cool’ Britain while tracing the search for identity of the young protagonists in multicultural London.